A multicenter study: how do medical students perceive clinical learning climate?. Issue 1 (1st January 2016) - Yilmaz, Nilufer Demiral; Velipasaoglu, Serpil; Ozan, Sema; Basusta, Bilge Uzun; Midik, Ozlem; Mamakli, Sumer; Karaoglu, Nazan; Tengiz, Funda; Durak, Halil İbrahim and Sahin, Hatice
Abstract : Background: The relationship between students and instructors is of crucial importance for the development of a positive learning climate. Learning climate is a multifaceted concept, and its measurement is a complicated process. The aim of this cross-sectional study was to determine medical students' perceptions about the clinical learning climate and to investigate differences in their perceptions in terms of various variables. Methods: Medical students studying at six medical schools in Turkey were recruited for the study. All students who completed clinical rotations, which lasted for 3 or more weeks, were included in the study ( n =3, 097). Data were collected using the Clinical Learning Climate Scale (CLCS). The CLCS (36 items) includes three subscales: clinical environment, emotion, and motivation. Each item is scored using a 5-point Likert scale (1: strongly disagree to 5: strongly agree). Results: The response rate for the trainees was 69.67% ( n =1, 519), and for the interns it was 51.47% ( n =917). The mean total CLCS score was 117.20±17.19. The rotation during which the clinical learning climate was perceived most favorably was the Physical Therapy and Rehabilitation rotation (mean score: 137.77). The most negatively perceived rotation was the General Internal Medicine rotation (mean score: 104.31). There were significant differences between mean total scores in terms of trainee/intern characteristics, internal medicine/surgical medicine rotations, and perception of success. Conclusion: The results of this study drew attention to certain aspects of the clinical learning climate in medical schools. Clinical teacher/instructor/supervisor, clinical training programs, students' interactions in clinical settings, self-realization, mood, students' intrinsic motivation, and institutional commitment are important components of the clinical learning climate. For this reason, the aforementioned components should be taken into consideration in studies aiming to improve clinical learning climate.